2015
DOI: 10.1002/star.201500098
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural properties of hydrophilic CdTe quantum dots in cationic starch polymeric matrix

Abstract: In this work, water soluble CdTe quantum dots (QDs) were incorporated into a biopolymeric matrix of polyacrylamide grafted onto cationic starch (CS-g-PAAm) to enhance optical properties of QDs. To this aim, the effect of various factors such as AAm concentration, molar ratio of CS-g-PAAm/CdTe, reaction temperature and time on optical properties of obtained QDs were investigated via UV-visible (UV-vis) and fluorescence spectra. Finally, the optimized QDs were characterized by Fourier transform infrared (FT-IR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In addition, the similar result has been demonstrated in Figure . It is indicated that channel 3 is the main pathway for forming RCS/AMs, which exactly corroborates the conjectured mechanism for CS/AMs formation in the experiments …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the similar result has been demonstrated in Figure . It is indicated that channel 3 is the main pathway for forming RCS/AMs, which exactly corroborates the conjectured mechanism for CS/AMs formation in the experiments …”
Section: Resultssupporting
confidence: 87%
“…More recently, great efforts have been made in synthesizing utility multisensitive hybrid hydrogels . Although a possible reaction mechanism was as well predicted by some related scholars, but it is different to understand the reaction mechanisms thoroughly unless we can obtain more details at the molecular level. In this work, the quantum chemistry theory will be used to simulate the reaction mechanism of chitosan and acrylamides (AMs, here it is AM or NIPAM) dimer, to study all possible reaction channels and reveal the underlying nature of polymerization at the micro level.…”
Section: Introductionmentioning
confidence: 89%